Toplumsal davranışın etmen temelli modellemesi: Organ bağışı örneği - Eren, Zafer (Lisansüstü Eğitim Enstitüsü, 2021)
İnsan davranışı ve insanlar arası etkileşimin ortaya çıkardığı sosyal sistemler olan toplum ve toplumsal olgular, doğası gereği karmaşık sistemlerdir. Karmaşıklık ve/veya sistem kuramı, sistemdeki öğelerin ayrık/özerk davranış, kural ve kararları ile sistemin diğer öğeleri arasındaki doğrusal ve doğrusal olmayan ilişkileri ifade etmesindeki yeteneği, öğelerinin etkileşimden ortaya çıkan sistemin anlaşılması, incelenmesi ve araştırılmasında diğer yöntemlere göre öne çıkmaktadır. Etmen temelli modelleme (Agent-based Modelling), ortaya çıkışı matematik ve hesaplamalı bilimlere dayanan, karmaşıklık ve sistem kuramı yaklaşımının modellenmesinde kullanılan görece yeni bir yaklaşım/yöntem ve araştırma alanıdır. Etmen temelli modelleme ile mikro düzeyde gerçekleşen davranış ve etkileşimlerin sonucunda, makro düzeyde beliren örüntüleri göstermek mümkündür. Bu da sosyal sistemlerin daha gerçekçi resmedilmesi, öğeleri arasındaki ilişkilerin modele yansıtılması, mikro-makro düzeyde gerçekleşen olayların aydınlatılmasında daha elverişli bir yol sunmaktadır. Bu çalışma kapsamında sosyal bir sorun, etmen temelli modelleme ile incelenmiştir. Etmen temelli modellemenin sosyal araştırmalar için can alıcı avantajı, yapay deney ortamı yaratmasıdır. Sosyal olgular için, doğa bilimlerinden farklı olarak, deney düzeneği kurmak maddi, fiziksel ve etik açıdan imkansız, zor ve maliyetli olduğundan etmen temelli modelleme, sunduğu yapay deney düzeneği ile araştırmanın ilerlemesini sağlamaktadır. Çalışmada, toplumsal bir sorunun ele alınması ile yaklaşımın sosyal boyutuna katkı sunulurken toplumsal bir sorunun çözümü yolunda ilerlenmiştir. Bu doğrultuda, araştırma konusu olarak Türkiye'de organ bağışı davranışının toplumsal örüntüsü araştırılmıştır. Tıp ve teknolojideki ilerlemeler doğrultusunda, bugün işlevini yerine getirmeyen organların kadavra/canlı başka bir bedenden alınanın nakil edilmesi ile organ yetmezliğinden muzdarip hastaların tedavi edilmesi mümkün hale gelmiştir. Bugün dünyada organ yetmezliği olan hastaların tedavisindeki kısıtlardan biri, yeterli kadavra organ bağışının olmamasıdır. Gelişmiş ülkelerde milyon nüfus başına düşen %30-40 düzeylerindeki organ bağışı oranları Türkiye'de %5-15 arasındadır. Gelişmiş ülkelerde gerçekleşen organ nakli operasyonlarında organ kaynağının %80'i kadavra iken Türkiye'de bu oran %20'dir. Çalışma kapsamında, öncelikle insan davranışı, davranış kuramları, organ bağışı davranışı ve literatürdeki çalışmalar incelenmiştir. Etmen temelli modelde, etmenlerin davranışlarının temel çerçevesi Planlı Davranış Kuramı'na (Theory of Planned Behavior) dayandırılarak kurgulanmıştır. Planlı Davranış Kuramı'na göre istemli bir davranışı gerçekleştirmeden önce bu davranış gerçekleştirmeye dair bir niyet vardır. Niyetin ise öznel norm, tutum ve algılanan davranışsal kontrol olmak üzere üç öncülü bulunmaktadır. Bu öncüllerin arka planında ise toplumsal ve psikolojik etmenler yer almaktadır. Organ nakli ve bağışı konusundaki literatür incelemesi sonucunda organ bağışı davranışının kavramsal bir modeli oluşturulmuş, kavramsal model etmen temelli benzetim modeline aktarılmıştır. Öznel norm, kişinin önemsediği, görüşlerine değer verdiği insanlardan algıladığı toplumsal baskıdır. Kişi, bu kişi ve gruplarla normlarını, değerlerini ve bazı demografik özellikleri paylaşmaktadır. Literatürde görülmüştür ki eğitim düzeyi ve gelir arttıkça organ bağışçısı olma olasılığı artmaktadır. Eğitim düzeyi, gelir durumu etmenin öznel normuyla ilişkilendirilerek, etmen toplumu dört eğitim düzeyi (ilköğretim mezunu olmayan, ilköğretim, ortaöğretim ve yükseköğrenim), üç gelir düzeyi (düşük, orta, yüksek) ve iki norm kategorisi (olumlu ve olumsuz) olmak üzere 24 gruba bölünmüştür. Grupların nüfus oranlarını belirlemek için Türkiye istatistikleri kullanılmıştır. Bireylerin aile üyesi, arkadaş, iş arkadaşı, politikacı vb. diğer bireylerle kurduğu ilişkiler farklılık göstermektedir. Bundan ötürü modelde etmenler için yüz yüze ve samimi ilişkilerin kuruluğu yakın çevre ve daha resmi ilişkilerin kurulduğu uzak çevre olmak üzere iki çevre tanımlanmıştır. Yakın çevrede kurulan ilişkiler karşılıklı iken uzak çevre için bu zorunlu değildir. Yine her etmenin ilişki kurduğu etmen sayısı aynı değildir ki bu sayıların Dunbar'ın çalışmalarından yola çıkılarak yakın çevre için Düzgün[5;15] dağılımdan geldiği, uzak çevre için Düzgün[45;135] dağılımdan geldiği kabul edilmiştir. Birey, yakın çevresi ile aynı sosyo-ekonomik grup içerisinde yer aldığından yakın çevresine ait etmenler kendi grubundan rastgele seçilirken uzak çevresine ait etmenler tüm toplumdan rastgele seçilmektedir. Etmenlerin öznel normu [0;1] arasında sürekli bir değişken olarak tanımlanmıştır. 0 'organ bağışlanmamalı' normunu temsil ederken 1 'organ bağışlanmalı' normunu temsil etmekte; 0,5 eşik değer olmaktadır. Etmenler başlangıçta gruplarına göre [0;0,5] veya [0,5;1] arasında rastgele bir norm almaktadır. Modelde daha sonra etmenin norm değişimi yakın ve uzak çevresindeki etmenlerle etkileşimin bir sonucu olarak hesaplanmaktadır. Organ bağışı niyetinin bir diğer bileşeni olan tutum ise Planlı Davranış Kuramı'na göre bilgi edinme yoluyla değişebilmektedir. İnsanların organ nakli ve bağışı konusunda edinecekleri, maruz kalacakları tüm olumlu ve olumsuz bilgiler tutumlarını etkilemektedir. Kamu spotları, kurumsal eğitimler, yazılı, görsel ve sosyal medya, sinema, TV dizileri vb. sistemsel olarak tek bir bilgi kaynağı olarak kabul edilmiştir. Organ yetmezliği ile sonuçlanabilecek bir kronik rahatsızlığa sahip olmak ya da organ nakline ihtiyaç duyan tanıdıklarının olması, bireylerin organ nakli ve bağışı konusunda bilgilendikleri diğer kaynaklardır. Etmenlerin tutumu [0;1] arasında sürekli bir değişken olarak tanımlanmıştır ve 0 'organ bağışı ile ilgili olumsuz tutumu' ifade ederken, 1 'organ bağışı ile ilgili olumlu tutumu' ifade etmektedir. Etmenler bu aralıkta rastgele bir tutum değeri almakta ve sistemdeki olumlu ve olumsuz bilgi, etmenin sağlık durumu ve organ nakline ihtiyaç duyan tanıdıkları sayesinde tutumları değişmektedir. Kamu spotları, filmler, organ bağışı etkinlikleri vb. olumlu bilgileri üreten olumlu bilgi fonksiyonu Beta(7;3), organ mafyası, şehir efsaneleri gibi olumsuz bilgileri üreten olumsuz bilgi fonksiyonu Beta(3;7) olarak belirlenmiştir. Sistemdeki bilgiye her etmenin aynı derecede maruz kalmadığı, etmenden etmene farklılık göstermesini sağlayan maruziyet fonksiyonu tanımlanmıştır. Olumlu ve olumsuz bilginin etmenler üzerinde etkisinin farklı olmasından ötürü olumsuz bilginin etmenler üzerinde olumlu bilgiden daha etkili olduğu, bu etkilerin etmenin eğitim düzeyine göre de farklılaştığı kabul edilmiştir. Algılanan davranışsal kontrol, modelde [0;1] arasında tanımlanmıştır. Her etmen için başlangıçta bir kereliğine belirlenmekte ve etmenin ömrü boyunca aynı değerde kalmaktadır. Benzetim modelinin sonuçları incelendiğinde Türkiye'nin 2012 yılında 0,002'den 2019 yılında 0,14'e çıkan bağışçı oranına (bağışçı/nüfus) benzer sonuçlar veren öznel norm ağırlığı 0,4, tutum ağırlığı 0,5 ve algılanan davranışsal kontrol ağırlığı 0,1 parametre değerleri belirlenmiş, model 100 kez koşturulmuştur. Organ bağışçıları incelendiğinde öznel norm ve tutumu düşük değerlerinden bağışçılar ortaya çıkmaz iken küçük ağırlığından ötürü düşük algılanan davranışsal kontrolü olan bağışçılar da ortaya çıkmıştır. Bağışçıların yaş dağılımları incelediğinde en fazla bağışçı %45 ile 20-44 yaş aralığında ortaya çıkmıştır. Bağışçıların yaş gruplarına dağılımı ile gerçek verilerle bir örtüşme olduğu görülmüştür. Benzetim sonuçlarından hareketle, Türkiye'de organ bağışı sayılarının önümüzdeki yirmi yıl boyunca artmaya devam ettiği, otuzuncu yıldan sonra ise %21 civarında küçük salınımlar yaptığı görülmüştür. Benzetim modelinin geçerliliği ortaya konulduktan sonra organ bağışı sayılarını artırmak için izlenebilecek politikalar için senaryolar oluşturulmuştur. İlk senaryoda bireylerin organ bağışına yönelik tutumlarının yükseltilmesi denenmiştir. Sistemdeki bilgi kaynaklarından çıkan olumlu bilgi miktarı Beta(7;3) fonksiyonu, Beta(10;3) ve Beta(12;2) fonksiyonları olarak güncellenmiş ve sonuçlar incelenmiştir. Sonuçlarda bağışçı oranlarının Beta(10;3) dağılımından gelen olumlu bilgi ile önümüzdeki yirmi yıl daha artmaya devam ederek otuzuncu yıldan sonra 0,24 civarlarında seyrettiği, Beta(12;2) dağılımından gelen olumlu bilgi ile önümüzdeki yirmi yıl daha artmaya devam ederek otuzuncu yıldan sonra 0,27 civarlarında seyrettiği görülmektedir. Sistemdeki olumlu bilgi miktarını artırmak organ bağışı sayılarını artırmıştır. Yine bireylerin tutumlarını olumlu yönde artırmak için ikinci senaryo, MEB müfredatında 9. sınıflar için yer alan Sağlık ve Trafik Kültürü adlı derste öğrencilere organ nakli ve bağışı konusunda bilgi aktarılmasıdır. Öğrencilerin bu dersten kazanımları olarak olumlu bilgi miktarlarının arttığı deneyler tasarlanmıştır. On altı yaşını tamamlamış ve eğitim düzeyi ortaöğretim ve üstü olan bireylerin tutumları 0,1 arttırıldığında bağışçı sayılarında anlamlı bir artış gerçekleşmez iken 0,3 ve üzeri artışlar ile bağışçı sayılarında anlamlı artışlar gerçekleşmektedir. Üçüncü senaryo ise ilk iki senaryonun birleştirilmesi ile kurgulanmıştır. Bu senaryonun ilk deneyi dolarak sistemdeki bilginin Beta(10;3) fonksiyonundan üretilmesi ve 9. sınıf öğrencilerinin aldıkları sağlık dersindeki eğitim ile tutumlarında 0,3'lük artış olduğu deney tasarlanmıştır. Uzun vadede bağışçı oranları 0,25 civarında salınmaktadır. Sistemdeki bilginin Beta(12;2) fonksiyonundan üretilmesi ve 9. sınıf öğrencilerinin aldıkları sağlık dersindeki eğitim ile tutumlarında 0,7'lik artış olduğu deneyin sonuçlarına göre ise bağışçı oranları 0,29 civarında salınmaktadır. Etmen temelli modelleme ile organ bağışı sayılarını arttırarak yetersizliği azaltmak gibi toplumsal bir sorun ele alınmış, organ bağışına yönelik, bireyin sosyal ve psikolojik güdülerine dair çıkarımlarda bulunulmuştur. Bağış sayılarını artırmak için izlenebilecek politikalar gerçek bireyler yerine yaratılan yapay bireyler ve toplumlar üzerinde denenerek elde edilebilecek sonuçlar irdelenmiştir. Etmen temelli model, sosyal olgu ve toplumsal sorunların çözümünde yapay ortam sağlamasının yanı sıra bireyin davranışının sosyal ve psikolojik temellerinin kavranması, olumsuz davranışı değiştirmek, olumlu davranışı pekiştirmek adına yapılabilecek müdahalelerin bir seyrini sunmaktadır.

Society and social phenomena, which are social systems formed by the interaction of human beings and human behaviours, are inherently complex systems. Complexity or system theory has become prominent to understand, discover and formalise complex systems that are the result of linear and nonlinear interactions, behaviours and rules of their autonomous units. Agent-based modelling (and simulation) (ABM/ABMS), whose roots are based on mathematics and computational science, is a relatively novel approach/method /research area to the modelling of complex systems, especially the social systems. Agent-based modelling makes it possible to demonstrate the interaction of individual agents and provides insights on a social phenomenon that was observed at macro level emerging from micro level behaviour. Agent-based modelling provides a tool to reflect the interactions of units and it enlightens the macro level complexity emerged from micro level and demonstrates it more realistically. Apart from being a powerful tool in social science, agent-based modelling is a research area that is a unique cross fertilization between computational and social sciences. While advances in mathematics, computational science (simulation, artificial intelligence, etc.) contribute to and develop this approach, theories and concepts in social science extend its boundaries to overcome new research challenges. Furthermore, agent-based modelling in social science has the potential to create a unique lab for social experiments. Within the scope of this study, the main purpose is to build an agent-based model of a social problem. The crucial advantage of agent-based modelling creates an artificial society to carry out experiments in a test environment. Different from the natural sciences, setting up experimental environments for social sciences is difficult since costs are too high and conducting experiments are sometimes impossible or unethical in human societies. Agent-based models provide a way to carry out quite impossible or unethical experiments in artificial societies rather than human societies and make progress for social researchers. In this study, organ donation shortage in Turkey was chosen as the social problem and an agent-based model of the social behaviour pattern in the case of organ donation was built. Advances in medicine and technology render it possible to transplant healthy organs which are harvested from a cadaver/living to substitute for malfunctioning organs to treat patients who are suffering from organ failure. Today all over the world, one of the constraints in the treatments of organ failure patients is the organ shortage or insufficient cadaveric organ donation. Organ donation rate is 30-40% per million population (pmp) in developed countries while it is only 5-15% pmp in Turkey. However, global transplantation numbers show that Turkey is at top of the liver and kidney transplantations. Compared to liver and kidney transplantations from a living donor, the total number of transplantations is lower. 80% of the organ transplantations are cadaveric in developed countries, whereas this percentage reduces to 20% for Turkey. Within the scope of this study, human behaviour, behavioural theories, organ donation behaviour and studies in the literature were reviewed, researched and analysed. The basic framework of agent behaviour in the agent-based model is built upon Theory of Planned Behavior by Icek Ajzen and Martin Fishbein. Theory of Planned Behavior assumes that a person has an intention to perform (or not to perform) a volitional behaviour and intention has three antecedents, namely subjective norm, attitude toward the behaviour and perceived behavioural control. Attitude is an individual's positive and negative evolution of performing the behaviour and a function of behavioural beliefs. Subjective norm, a function of normative beliefs, is a person's beliefs and perceived social pressure from certain individuals or group about performing his/her behaviours. As a function of control beliefs, perceived behavioural control is the perception on the capacity to carry out the behaviour. Thus, these behavioural, normative and control beliefs are based upon and spring from a profound background consisting of social, individual, cultural and informational factors. A conceptual model was built based on the transplantation and organ donation literature. An agent-based simulation model was generated according to the conceptual model. Subjective norm is a person's perceived social pressure from important people or groups that he/she shares the same norms, values and sometimes demographics with. In the related literature, education and income are the most prominent demographic factors that are positively associated with organ donation. People with higher educational and socio-economic status tend to be organ donor compared to those with lower educational and socio-economic status. These background factors are associated with the agent's subjective norm. Hence, the agent's society is divided into 24 groups with respect to four educational levels (no primary education, primary education, secondary education, and higher education), three income level (low, medium, high) and two norm categories (positive and negative). Group population rates are decided according to Turkey's demographics. Individuals contact family members, close friends, teachers, colleagues, acquaintances, politicians, or celebrities in different ways. Therefore, two neighbourhoods for each agent in the model are defined: the close circle in which face to face, close and more intimate relationships are established and the distant circle in which relationships are more formal and ties are weaker. Relationships in the close circle are mutual, but the ones in the distant circle do not have to be so. Since individuals have different personalities such as introvert or extrovert, agents can have different numbers of relations. Dunbar's studies guided us to decide on how many relations agents can establish. The number of relations an agent can have was assumed to be Uniform(5;15) in his/her close circle and Uniform(45;135) in his/her distant circle. Since an agent would share the same education level, socio-economic level and norm with those in his/her close circle, values of the factors for his/her close circle were chosen randomly from the levels of the agent. However, those for his/her distant circle were chosen from the whole society randomly. An agent's subjective norm in the model was assumed to be a continuous random variable that takes values over the interval [0;1]. The lower bound (0) corresponds to the case 'should not be a donor', whereas the upper bound (1) indicates the case 'should to be a donor', and 0.5 is the threshold. At the beginning, an agent's norm is randomly selected from either the real interval [0;0.5) or the real interval [0.5;1] based on his/her norm category. Then, the agent's subjective norm changes by his/her interactions with other agents that are in his/her close or distant circle. According to the Theory of Planned Behavior, attitude, which is another determinant of intention, changes through information retrieval. When people are exposed to positive or negative information about organ donation, their attitude changes. Information resources such as public service announcements, corporate trainings, printed media, visual media, social media, movies, and TV shows were considered as a single source of information from a systematic point of view. People that are suffering from health problems that can cause organ failure or that know people who are on the organ waiting list also retrieve more information on the subject. Hence, an acquaintance on the organ waiting list and the person's health condition are other information resources. Agent's attitude is assumed to be a continuous random variable taking values over the real interval [0;1] in the model. The lower bound (0) represents the case of having a 'negative attitude about being an organ donor', the upper bound (1) represents the case of having a 'positive attitude about being an organ donor'. The agent's attitude was determined randomly at the beginning, and then it is changed according to the positive and negative information available in the system, agent's health and agent's relations with his/her acquaintance(s) on the organ waiting list. Positive information, which is supportive information about organ donation retrieved through public announcements, movies, organ donation events, corporate trainings and negative information generated by urban legends and organ mafia are system variables that are independent from agents. Positive information was assumed to be Beta(7;3) and negative information was assumed to be Beta(3;7). Since the agents are exposed to the positive and negative information randomly, the level of exposure is not the same for all agents. This is why an exposure function was defined. Since the effects of positive information differ from those of negative information, negative information was assumed to affect the agents more significantly and these effects are assumed to differ across education levels. More educated agents evaluate positive information as more reliable, but negative information as more suspicious. Agent's perceived behavioural control was also assumed to be a continuous random variable taking values over the real interval [0;1] in the model. It was assumed not to be associated with any of the background factors. An agent's perceived behavioural control was determined randomly at the beginning and it is assumed to remain the same throughout his/her lifetime. Setting the subjective norm weight at 0.5, the attitude weight at 0.4 and the perceived behavioural control weight at 0.1 returned simulation results overlapping actual data on organ donation in Turkey between 2012-2019. The model was run 100 times and the simulation results indicated no donors with low subjective norm and attitude, but there were donors with low perceived behavioural control. Most of the donors (45%) were found in the 20-44 age range and the mean age of donors was found as 48. Besides, the distribution of donor ages is similar to the actual distribution in Turkey. The simulation indicated that the donor rate would continue to increase in the next twenty years and then stabilize around 21% after thirty years. There are three experiments designed to specify policies that can increase the number of organ donations in this study. The first scenario focuses on increasing the positive information in the system. The positive information function is Beta(7;3) in the agent-based simulation model (Base model). It becomes Beta(10;3) in Experiment1 and Beta(12;2) in Experiment2 and the models were run 100 times. The simulation results showed that donation would increase in the next twenty years and stabilize around 24% in Experiment1 and around 27% in Experiment2. Both experimental results showed that increasing positive information such as public announcements, news, corporate trainings in the system would result in a significant increase in the number of organ donations. The second scenario considers the inclusion of course subjects regarding organ transplantation and donation in the Health and Traffic course available in the curriculum for 9th graders designed by the Ministry of Education in Turkey. Experiments in which the amount of positive information students retrieved through this course were designed. The attitude was increased by 0.1 in Experiment3, by 0.3 in Experiment4, by 0.5 in Experiment5, and by 0.7 in Experiment6 for agents who completed at least secondary education and were at least 16 years old. Running the models ran 100 times, we found that increasing attitude by 0.1 did not results in a significant increase in the number of organ donors, but increasing it 0.3 or more did. The third scenario is a combination of the first and second scenarios. In Experiment7, the positive information function is Beta(10;3) and attitude is assumed to increase by 0.3 through the course. The model was run 100 times and the simulation results showed that the organ donation rate would stabilize around 25% in Experiment7. The positive information function is Beta(12;2) and the increase in positive attitude through the course was assumed to be 0.7 in Experiment8. The model was again run 100 times and the simulation results showed that the organ donation rate would stabilize around 29% in Experiment8. Both experimental results suggested that increasing the positive information in the system and the individual's knowledge on organ donation would result in a significant increase in the number of organ donors. In this study, organ shortage and low donation rates were considered as a social problem and an agent-based model was built to increase the number of organ donors. The model has a couple of assumptions on social and psychological motivations and factors. The simulation results also provide some individual and social insights on being donor. Various policies on how to increase the donation rates were discussed via simulation results carrying out the model on an artificial society rather than a real one. The simulation results also provide long-term predictions of this social problem. Offering alternatives and adoptable policies with long-term predictions, the study can assist practitioners, policy makers and strategists in making more reliable decisions without having to implement the model in the real world. Beside providing an artificial environment to investigate social phenomena and problems, agent-based modelling is a novel approach that can be adopted to comprehend social and psychological roots and/or factors of the social behaviour of an individual. Thus, it can provide new and more profound research areas, knowledge and approaches that consider the reinforcement of positive behaviour and the alteration of negative behaviour.
Agent based modeling of social behaviour: The case of organ donation
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2021
Keywords: Planlanmış davranış; Planned behavior; Sağlık davranışı etkileşim modeli; Health behavior interaction model; Sağlık politikası; Health policy